STIMULATING EARLY CHILDHOOD CREATIVITY THROUGH A LOCAL WISDOM–BASED COOKING CLASS PROGRAM - Yuliawati, Nurma; Trianggono, Mochamad Maulana; Triana, Rizki Sevi (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
This research aims to provide an in-depth description of stimulating creativity in early childhood through local wisdom-based cooking class activities at KB Rahmatan Lil Alamin, Lampeji. This study uses a qualitative descriptive approach with data collection techniques through participatory observation, structured interviews, and documentation. The cooking class activity is designed by combining the cooking learning process and the introduction of local cultural values through the activity of decorating traditional Apem cakes. Research results show that this activity effectively stimulates four aspects of creativity, namely fluency, flexibility, originality and elaboration). In addition to enhancing creativity, this activity also fosters appreciation for local cultural heritage and strengthens children's social interactions with teachers, peers, and parents. These findings indicate that local wisdom-based cooking classes can be implemented as a contextual, holistic, and meaningful learning strategy to optimize the creativity potential of early childhood.